Toxic warfare - Karasik, Theodore William (Rand, 2002)
Since the 1990s there has been an increase in the use of toxic weapons; for example, inexpensive and easily acquired chemicals and industrial waste. This work examines the implications of toxic weapon use for military planning and concludes that such weapons merit further analysis.